Санітарна якість сиру кисломолочного різних виробників - Білан, Марина Володимирівна; Bilan, Maryna; Bilan, M. V.; Щурінова, Марина Максимівна; Shchurinova, Maryna; Приданцев, Сергій Олександрович; Pridantsev, Sergiy (Національний фармацевтичний університет, 2020)
Молочні продукти були, є і завжди будуть популярними, оскільки є корисними, складають основу для дитячого і дієтичного харчування. Одним з таких продуктів є кисломолочний сир, який виробляють шляхом сквашування пастеризованого молока чистими культурами молочнокислих бактерій із застосуванням або без застосування хлористого кальцію, сичужного ферменту і видаленням із згустку частини сироватки. Він багатий білком, жиром, мінеральними речовинами, особливо кальцієм і фосфором. Усі ці корисні складові переходять в сир з молока і легко засвоюються організмом. Ще одна користь сиру полягає в тому, що це живий кисломолочний продукт, такий же живий, як йогурти і кефір. Sour milk cheese is one of the most valuable fermented milk products, which is very useful for the human body in terms of its biological properties. The problem of high quality is one of the main tasks of economic development of our country. In recent years, all technically advanced countries have shown a growing interest in improving the quality not only of sour milk cheese, but also, in general, of sour milk products. It was found that the organoleptic parameters (color, taste, smell, consistency) samples of sour milk cheese complied with regulatory documentation, although one of the manufacturers did not specify the latter. The total number of mesophilic lactic acid bacteria (CFU in 1 g) in all samples ranged from 7 × 106 to 9 × 106. No BGKP and pathogenic microorganisms (genera Salmonella, Staphylococcus) were detected. However, two samples of cheese showed the presence of enterococci (9 and 114 CFU per 1 g), and one sample exceeded (> 100 CFU per 1 g) the number of yeast cells.
Sanitary quality of sour milk cheese from different manufacturers
Білан Марина Володимирівна https://orcid.org/0000-0003-3178-201X
Keywords: ентерококи; enterococci; сир кисломолочний; sour milk cheese; якість; quality; органолептичні показники; organoleptic characteristics; мезофільні молочнокислі бактерії; mesophilic lactic acid bacteria